UTILIZATION OF SOLAR POWER PLANTS AS AN ENERGY SOURCE FOR FISHING BOATS - Ahmad Taufik (Yayasan Sinergi Multidimensi Kreatif, 2025)
This research aims to utilize new and renewable energy widely. The use of diesel-fueled engines is still widely used among fishermen and in order to support the government in realizing green energy, it is necessary to provide electrical energy by utilizing new and renewable energy. One of the renewable energies that can be used is solar energy. Solar energy in the solar power plant system can be operated on boats by utilizing the roof of fishing boats. The solar power plant system is planned to use 15 units of solar panels with a capacity of 250 Wp, 1 unit of 120V 50A solar charge controller, 10 units of 12V 200Ah batteries, and a BLDC motor with a capacity of 6 kW. The total cost of solar power plant investment in the roof of a fishing boat as an energy source to replace a diesel engine is Rp. 94.000,000,- equivalent to the operational cost of a diesel engine for 1.26 years or about 1 year 3 months and 5 days.